Antioxidant and anti-inflammatory activity of capitula, leaf and stem extracts of Tanacetum cilicicum (Boiss.) Grierson - Aybeniz Yıldırım; Ali Şen; Ahmet Doğan; Leyla Bitis (International Journal of Secondary Metabolite)
In this study, various extracts obtained different parts of Tanacetum cilicicum were investigated for in vitro antioxidant and anti-inflammatory activity. Antioxidant activity was tested with three methods; namely 2.2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity, 2.2′‐azinobis (3‐ethylbenzothiazolin‐6‐sulphonic acid) (ABTS) radical cation scavenging capacity, and ferric-reducing antioxidant power (FRAP) assays. Total phenolic and flavonoid contents of extracts were determined by Folin-Ciocalteu and aluminum chloride methods, respectively. Also, anti-inflammatory activity of these extracts was evaluated by 5-lipoxygenase inhibition assay. Ethyl acetate extract of capitula of T. cilicicum (TCCEA) showed the highest antioxidant activity with IC50 values of 22.44 and 30.86 µg/mL against DPPH and ABTS radicals, respectively. At the same time, the highest ferric reducing power was found in the TCCEA (42.2 mg TE/g extract). The highest total phenolic contents have been detected in TCCEA and ethyl acetate extract of leaves of T. cilicicum (TCLEA) with value of 174.1 and 175.6 mg GAE/g extract, respectively. Similarly, the highest total flavonoid contents have been detected in TCCEA and TCLEA with values of 26.94 and 30.48 mg QE/g extract, respectively. TCCEA exhibited strong anti-inflammatory activity with IC50 value of 9.44 µg/mL when compared to standard indomethacine (22.39 µg/mL). These results demonstrate that TCCEA has a significant antioxidant and anti-inflammatory activity. Also, the results show that TCCEA is a good candidate for further bioactivity-guided fractionation in the search for new active anti-inflammatory and antioxidant compounds.